Setting limits fairly - Norman Daniels (Oxford University Press, 2008)
The central idea behind this book is that we lack consensus on principles for allocating medical resources, and in the absence of such a consensus we must develop and rely on a fair decision-making process for setting limits on health care. The authors provide an analysis of the current situation, reviewing typical solutions, before describing their own approach. The audience for the book is global since the problem of limited resources cuts across all types of health care systems whether or not they have universal coverage